PENGARUH KEPEMIMPINAN, MODAL PSIKOLOGIS, DAN KEADILAN ORGANISASI TERHADAP KINERJA PEGAWAI - Hariani, Mila; Darmawan, Didit (Jurnal Ilmiah Satyagraha, 2025)
This study aims to analyze the effect of leadership, psychological capital, and organizational justice on employee performance. Data were obtained from 100 respondents working in manufacturing companies in Surabaya through survey method and analyzed using multiple linear regression. The results showed that the three independent variables have a significant influence on employee performance, with the largest contribution coming from leadership. Psychological capital supports individual performance through strengthening self-efficacy, optimism, hope, and resilience, while organizational justice also strengthens employee performance by contributing to the organization. This study suggests the development of transformational leadership programs, psychological capital development training, and consistent justice policies to improve overall employee performance.